Kazantzakis, un intellectuel à l'épreuve de la réalité - Gunnar De Boel (Cahiers Balkaniques)
For Kazantzakis, Askitiki is not just an abstract metaphysics; its anti-humanistic ideas are also used to interpret contemporary reality. Only when he is confronted with the misery that results from their application in reality, he abandons them and becomes a real writer.